Assessment of Sample Size Calculations Used in Aquaculture by Simulation Techniques - de Blas, Ignacio; Muniesa, Ana; Vallejo, Adriana; Ruiz-Zarzuela, Imanol (Frontiers in Veterinary Science, 2020)
An adequate sampling methodology is the key to know the health status of aquatic populations. Usually, the aims of epidemiological surveys in aquaculture are the detection of an infection and the estimation of the disease prevalence, and different formulas are used to calculate the sample size. The main objective of this study was to assess if the sample sizes calculated using classical epidemiological formulas are valid considering the sampling methodology, the population size and the spatial distribution of diseased animals in the population (non-clustered or clustered). However, it is widely accepted in aquaculture the use of sample sizes of 30, 60 and 150 fish, according to requirements of the World Organisation for Animal Health (OIE) for epidemiological surveillance. We have developed a specific software using ASP (Active Server Pages) language and MySQL database in order to generate aquatic populationsfrom 100 to 10 000 brown trouts infected by Aeromonas salmonicida with different prevalences: 2, 5, 10 and 50%. Then we have implemented several Monte Carlo simulations to estimate empirically the sample sizes corresponding to the different scenarios. Furthermore, we compared these results with the values calculated by classical formulas. We determined that simple random sampling was more accurate in order to detect an infection since they are independent of the distribution of infected animals in the population. However, if diseased animals are non-clustered it is more efficient to use systematic methods, even in the case of small populations. Finally, the formula to calculate sample size to estimate the prevalence is not valid when the expected prevalence is far from 50%, and it is necessary to increase the sample size to reach the desired precision.